PENERAPAN METODE AL-QOSIMI DALAM MENINGKATKAN KUALITAS HAFALAN PESERTA DIDIK PADA MATA PELAJARAN TAHFIDZ KELAS IX DI SMP IT AL-ISLAH PUTRA KABUPATEN MAROS - Batara, Muh; Nurlaelah; Karim, Bisyri; Wahab, Abdul; Syaripuddin, Said (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Al-Qosimi method in Tahfidz learning and to determine the improvement in the quality of students' Qur'an memorization after the method was applied in class IX of SMP IT Al-Islah Putra, Maros Regency. This research employed Classroom Action Research (CAR) carried out in two cycles, with each cycle consisting of planning, action, observation, and reflection. The subjects were 48 male students of class IX. Data were collected through observation, tests, interviews, and documentation, then analyzed descriptively using percentage and mean-score formulas. The results showed that the implementation of the talaqqi, aradh, and muraja'ah stages of the Al-Qosimi method improved students' memorization quality. Observation scores rose from 60.14% (poor) in the pre-cycle to 71.11% (fair) in cycle I and 85.56% (good) in cycle II. Test scores likewise increased, with the class average rising from 61.2 to 76.7 and finally to 86.5, while the completion rate rose from 29.1% to 60.4% and reached 97.9% in cycle II, with 47 of 48 students meeting the minimum mastery criterion. These findings indicate that the Al-Qosimi method, through its systematic and repetitive stages, is effective in improving the fluency, articulation accuracy, tajwid application, and verse-order accuracy of students' memorization. It is concluded that the Al-Qosimi method is an effective alternative strategy for improving the quality of Qur'an memorization in Tahfidz learning.